Advances in financial economics. Vol. 16 - Ferris, Stephen P.; Kose, John (Advances in financial economics ;, 2013)
This volume contains a set of empirical papers by a set of global scholars who examine corporate governance and market regulation from a variety of perspectives. Jiang, Kim and Zhang argue that in certain cases an ex post increase in CEO pay can prevent the ex ante problem of managerial underinvestment and thereby help to reduce the agency problems characteristic of modern firms. Akyol and Cohen focus on firms use of executive search firms versus allowing internal members to nominate new directors to serve on the board of directors. Choi, Ferris, Jayaraman and Sabherwal examine 361 CEO terminations occurring among the Fortune Global 500 firms during the years 2000 to 2006. Cashman, Gillan and Whitby investigate the labor market for corporate directors to better understand which director attributes are relevant for board selection. Baulkaran, Amoako-Adu and Smith analyze the link between the valuation discount of dual class companies and the channels through which private benefits can be extracted. Aggarwal examines ETFs and notes that the additional risks, complexity, and reduced transparency of these funds have attracted heightened attention by regulators.